The role of antioxidant nutrients in mitigating PM2.5-related health risks in young Indian children - George, Franciosalgeo; Chaudhary, Ekta; Dey, Sagnik; Thomas, Tinku; Sachdev, Harshpal Singh; Kurpad, Anura; Ghosh, Santu (Frontiers in Public Health, 2025)
IntroductionPollution (PM2.5) exposure can result in acute respiratory illness (ARI) and anaemia in children. We aimed to investigate if antioxidant nutrient intakes could mitigate the impact of PM2.5 on child health outcomes on a national scale in India.MethodsWe triangulated satellite-derived PM2.5 exposure data at the primary sampling unit level, with ARI and anaemia prevalence data from national district-level survey, and antioxidant nutrient intakes from household food expenditure survey. Logistic mixed effects regression model was used to estimate the effect of PM2.5 at different levels of nutrient intake.ResultsThis study included 208,782 children with valid ARI and 197,289 children with valid hemoglobin measurements. The prevalence of ARI and anaemia were 2.8% (95% CI: 2.3, 3.2) and 57.6% (95% CI: 57.2, 57.9) respectively. The intake of selected antioxidant nutrients such as vitamin C, D, and selenium, when higher than their estimated average requirement (EAR), lowered the risk of ARI associated with high PM2.5 exposure, while intakes higher than the EAR of vitamins A, C, D, zinc, and selenium similarly lowered the risk of anaemia. In terms of foods, similar benefits were observed with daily consumption of small amounts of fruits and vegetables.ConclusionThe result of this study highlights the importance of antioxidant rich balance diet for neutralizing adverse health effects of air pollution exposure to some extent till the environmental policy of the country could reduce emission of hazardous pollutants below safe level for human health.